Mie Lidi Bayam Merah untuk Meningkatkan Haemoglobin pada Remaja Putri - Devi Aulia Rusli; Hullyatun Nufus; Kharanita Putri Andini; Siti Soviah; Lia Yuliani; Daini Zulmi (Jurnal Obstretika Scientia, 2022)
Anemia is a condition of the body in which the level of hemoglobin (Hb) in the blood is lower than normal. Adolescents have problems that are sometimes overlooked, for example iron deficiency, anemia in young women has an impact for now and in the future. Red spinach or in Latin it is called Amarathus tricolor L. It has benefits for the body. One of the benefits provided by red spinach is that it can prevent anemia because it contains iron, which is an important element for the formation of red blood cells. Red spinach can be used as an alternative ingredient to prevent anemia by doing something different in processing red spinach, namely by adding red spinach to the processing of noodle sticks. The purpose of this innovation is to increase hemoglobin levels in young girls. The method in this study was quantitative using a pre-experimental design in two groups with a pretest-posttest control group design technique. The population in this study were all female adolescents at La Tansa Mashiro Akbid level I and level II who experienced anemia, the total sample size was 42 people who were grouped into 2 groups, namely the control group and the intervention group, each group of 21 people. The results obtained from the control group were that 71.4% did not experience an increase in Hb and in the intervention group it was found that 90.5% of respondents experienced an increase in Hb. Suggestions for adolescents are expected to make efforts to prevent anemia by increasing knowledge about anemia and red spinach.